2020
DOI: 10.3390/s20092649
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Machine Learning Approach for Effective Recognition of Diabetes in E-Healthcare Using Clinical Data

Abstract: Significant attention has been paid to the accurate detection of diabetes. It is a big challenge for the research community to develop a diagnosis system to detect diabetes in a successful way in the e-healthcare environment. Machine learning techniques have an emerging role in healthcare services by delivering a system to analyze the medical data for diagnosis of diseases. The existing diagnosis systems have some drawbacks, such as high computation time, and low prediction accuracy. To handle these issues, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 50 publications
0
60
1
Order By: Relevance
“…The method was designed on a filtering method based on a decision tree algorithm. Experimental results have shown that the proposed performance of the system is comparable to previous state-of-the-art methods [21].…”
Section: Related Workmentioning
confidence: 70%
“…The method was designed on a filtering method based on a decision tree algorithm. Experimental results have shown that the proposed performance of the system is comparable to previous state-of-the-art methods [21].…”
Section: Related Workmentioning
confidence: 70%
“…As shown in Table 6 and Figure 12 , the receiver operating curve (ROC), the ROC is thetrue positive rate–false positive rate curve: the x -axis represents true; positive rate, the y -axis represents the false positive rate. From Figure 12 , we can see that the curve is very close to (0, 1) point [ 22 24 ]. Therefore, the classification accuracy of the prostate cancer machine-assisted diagnosis system is still very high.…”
Section: Experimental Performancementioning
confidence: 99%
“…Amin UI Haq et al [34] proposed the machine learning model to predict the diabetes disease at early stage. They concluded that machine learning can play vital role in the healthcare.…”
Section: Blood Pressurementioning
confidence: 99%